Taxonomy and immature stages of the Platystomatidae (Diptera: Tephritoidea) of Israel - Bodner, L.; Freidberg, A. (Zootaxa, 2016)
The Platystomatidae fauna of Israel is reviewed. Eleven species in two genera, Platystoma Meigen and Rivellia Robineau-Desvoidy, are recognized. Ten of the eleven species are recorded from Israel for the first time, and six of them are described as new: Platystoma dalia n. sp., P. elizabethae n. sp., P. geula n. sp., P. torridum n. sp., P. trigonum n. sp., and Rivellia israelica n. sp. Detailed descriptions, redescriptions, illustrations, and keys to all local platystomatid taxa are provided. The complete life-cycle of P. torridum n. sp. is reported, with descriptions and illustrations of egg, 3rd instar larva, and puparium.